Hooded knights on the Niagara the Ku Klux Klan in Buffalo, New York - Lay, Shawn (New York New York University Press, 1995)
"A notable case study of the second Ku Klux Klan in a northern industrial city. The author illuminates the origins and activities of the Buffalo Klan, the social and political context in which it operated, and the character of its membership. The book contributes to the current reevaluation of the KKK and to the scholarly literature on the 1920's." D.W. Grantham, Vanderbilt University
A troubled community -- The Kluxing of buffalo -- Fraternity, moral reform, and hate -- The knights of the Queen City -- The destruction of the Buffalo Klan
Includes bibliographical references (pages 151-175) and index.
Keywords: Ku Klux Klan (1915- ) -- New York (State) -- Buffalo -- History